Preferencje studentów w zakresie metod wykładowych (na przykładzie Politechniki Koszalińskiej) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of this study is to investigate the Polish students preferences of economic and non-economic specialties in the way of learning in lectures. The paper provides an answer to the following research question: how to teach students in the modern condition. Statistically proven that Polish students of economic and non-economic specialties do not prefer the auditory way of learning in lectures. The result is very highly statistically significant (99,9%). Statistically proven that the difference in the preferences of students of economic and non-economic specialties must be taken into account. The result is highly statistically significant (99,0%). The result of the study may be useful for changing of Polish Higher Education. It is necessary to equip all lecture halls with visual learning tools. It is necessary to train lecturers to use visual learning tools.
Keywords: student’s preferences, lecture, way of learning in lectures, auditory way, visual way